NURİ BİLGE CEYLAN’S NARRATIVES IN NEW TURKISH CINEMA: AN AUTO-ORIENTALIST APPROACH IN ONCE UPON A TIME IN ANATOLIA? OR A POST-ORIENTALIST NEGOTIATION? - Ertürk, Emre (Namik Kemal University, 2025)
This article explores the representation of “otherness” in New Turkish Cinema by examining Nuri Bilge Ceylan’s Once Upon a Time in Anatolia within the framework of Orientalism and post-Orientalism. It investigates whether the film’s portrayal of Anatolian rural life reinforces Orientalist discourse or reflects a post-Orientalist vision that redefines otherness through hybridity and cultural negotiation. Drawing on Homi K. Bhabha’s concepts of “hybridity” and the “third space,” the study argues that Ceylan’s depiction of otherness is neither externalized nor romanticized. Instead, it arises through coexistence marked by ambiguity, contradiction, and mutual interaction. The film’s spatial aesthetics invite viewers to question the boundaries between subject and object, center and periphery, East and West, while evoking a sense of being suspended between the finite and the infinite. Through this, Once Upon a Time in Anatolia transcends conventional Orientalist narratives by critiquing both Western perceptions of Turkey and Turkey’s internal construction of the “other.” Ceylan transforms the rural landscape from a site of exoticism into a “third space” of cultural and ideological exchange. The film thus reconfigures otherness as a dynamic process of interaction rather than a fixed opposition. Ultimately, it mediates between Orientalist and post-Orientalist discourses, encouraging audiences to reconsider both Anatolian identity and their own interpretive standpoint.